Iridium single-atom catalyst coupled with lattice oxygen activated CoNiO2 for accelerating the oxygen evolution reaction. Issue 48 (30th November 2022) - Yang, Meng-Qi; Zhou, Kai-Ling; Wang, Chao; Zhang, Man-Chen; Wang, Chang-Hao; Ke, Xiaoxing; Chen, Ge; Wang, Hao; Wang, Ru-Zhi
Abstract : An Ir single atom catalyst supported by oxygen vacancy-modulated CoNiO2 is constructed (IrSA -VO -CoNiO2 ), in which the oxygen vacancy coupling with Ir atoms in CoNiO2 facilitates the participation of lattice oxygens in OER. Abstract : Iridium (Ir) single-atom catalysts (SACs) exhibit extraordinary advantages in the oxygen evolution reaction (OER) owing to their unique electronic structure and maximized atom utilization. However, further developments have met with bottlenecks due to the limited catalytic activity derived from the widely adopted adsorbate evolution mechanism (AEM) pathway in Ir SACs for OER. Herein, we report an efficient strategy to improve the intrinsic activity of Ir SACs by anchoring atomic Ir on an oxygen vacancy-modified CoNiO2 support (IrSA -VO -CoNiO2 ), in which a more advanced lattice oxygen oxidation (LOM) pathway is constructed by activating lattice oxygen to participate in OER. Specifically, the synthesized CoNiO2 support could provide the weak metal–oxygen bond and facilitate the movement and conversion of lattice oxygen. The oxygen vacancies provided abundant active sites for the adsorption of OH* and induced a substantial O 2p characteristic near the Fermi level for activating the lattice oxygen in CoNiO2 . Moreover, the introduction of Ir atoms in the oxygen vacancies modulated CoNiO2 results in the significant overlap between the Ir 5d and O 2p bands and constructed a stronger Ir–O covalent bond, which extremely facilitated the transformation from O–O to OO* for boosting the final O2 evolution. Through the above-mentioned results, a more efficient LOM pathway in the single-atom Ir catalyst was constructed, and the as-synthesized IrSA -VO -CoNiO2 displayed outstanding OER performance with 10 mA cm −2 at a low overpotential of 183 mV and a high mass activity of 5 A mg −1 at the overpotential of 300 mV, significantly outperforming the reported catalysts. This work proposes an advanced channel to design efficient electrocatalysts for promising OER applications.